Occupation-constrained interband dynamics of a non-hermitian two-band Bose-Hubbard Hamiltonian - Muñoz-Arias, Manuel H.; Parra Murillo, Carlos Alberto; Wimberger, Sandro (Fluctuation and noise letters, 2017)
The interband dynamics of a two-band Bose-Hubbard (BH) model is studied with strongly correlated bosons forming single-site double occupancies referred to as doublons. Our model for resonant doublon interband coupling exhibits interesting dynamical features such as quantum Zeno effect, the generation of states such as a two-band Bell-like state and an upper-band Mott-like state. The evolution of the asymptotic state is controlled here by the effective opening of one or both of the two bands, which models decay channels.